Breast Cancer Screening Awareness and Participation Among Women in North India - Eric Kwasi Elliason; Atul Khajuria; Stephen Monday; J. Samuel Kamanda (International Journal of Women's Health Nursing And Practices, 2025)
Breast cancer is the most prevalent malignancy among Indian women, accounting for 25% of all female cancers (ICMR, 2020). Significant urban-rural disparities in screening persist across North India due to socioeconomic, cultural, and healthcare access barriers. This study evaluates these disparities to inform targeted interventions. A cross-sectional study was conducted among 1,500 women (750 urban, 750 rural) in Delhi, Uttar Pradesh, Punjab, and Haryana, using stratified random sampling. Data were collected via structured questionnaires (urban) and in-person interviews (rural) to assess awareness of symptoms and screening, participation in mammography and self-exams, and perceived barriers. Statistical analyses included chi-square tests, logistic regression (SPSS v22), and thematic analysis of qualitative responses. Urban women demonstrated significantly higher awareness of symptoms (65% vs. 50%, p<0.001) and mammography (72% vs. 50%, p<0.001). Screening participation was also higher among urban women for mammography (38% vs. 22%) and self-exams (55% vs. 40%, p<0.001). Financial constraints (40%) and lack of information (30%) were the predominant barriers in rural areas, while time limitations (27%) were most cited by urban women. Education (OR=3.5, 95% CI=2.1–5.5) and income (OR=2.8, 95% CI=1.8–4.3) were strong predictors of screening uptake. Findings highlight the urgent need for targeted interventions. Policy recommendations include subsidized rural screening, community-based awareness campaigns, and integration of breast self-exam education into primary care. Addressing socioeconomic and cultural determinants could reduce screening disparities by an estimated 40–50% over 5 years.
Keywords: Awareness; India; breast cancer; screening disparities; urban-rural